Mapping Leopardi poetic and philosophical intersections - Cervato, Emanuela; Epstein, Mark; Santi, Giulia, 1983-; Wright, Simona (Cambridge Scholars Publishing, 2019)
Are you curious about the private laboratory of Giacomo Leopardi, Italy's greatest modern lyrical poet? Interested in using expert maps to explore it, while deepening your acquaintance with one of the most creative materialist thinkers? This collection of essays makes very original use of the new translation of Leopardi's Zibaldone di pensieri and investigates its connections to all his other works. -- Provided by publisher.